2004
DOI: 10.1016/j.jtcvs.2003.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Extended septal myectomy for hypertrophic obstructive cardiomyopathy with anomalous mitral papillary muscles or chordae

Abstract: Hypertrophic obstructive cardiomyopathy associated with anomalous mitral papillary muscles or chordae can be successfully treated without mitral valve replacement by surgical relief of the anomalies and an extended septal myectomy; early mortality is low, obstruction and mitral regurgitation are significantly reduced, and late results are excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 21 publications
3
140
0
3
Order By: Relevance
“…Consequently, outflow tract obstruction and MR may persist after successful surgical myectomy. To counteract residual SAM, several authors (22)(23)(24) reported MV replacement as an alternative procedure in patients regarded as less suitable candidates for septal myectomy. In our institution, while we agree that the mitral valvular dysfunction is an integral factor in producing outflow obstruction, replacing the valve is not imperative either for reduction of the outflow gradient or for alleviation of mitral insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, outflow tract obstruction and MR may persist after successful surgical myectomy. To counteract residual SAM, several authors (22)(23)(24) reported MV replacement as an alternative procedure in patients regarded as less suitable candidates for septal myectomy. In our institution, while we agree that the mitral valvular dysfunction is an integral factor in producing outflow obstruction, replacing the valve is not imperative either for reduction of the outflow gradient or for alleviation of mitral insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…6 Septal myectomy is traditionally performed through an aortotomy, creating a rectangular trough (usually 3.5 to 5.0 cm in length) by 2 parallel longitudinal incisions in the basal septum (2 to 3.5 cm apart). These incisions are extended distally and connected just beyond the point of mitral-septal contact and obstruction (Morrow procedure) 5 or at the bases of papillary muscles (extended myectomy), 14 yielding a residual septal thickness of 8 to 10 mm and 3 to 15 g of septal muscle, and thereby enlarging the outflow tract and abolishing systolic contact between the mitral valve and the septum. 3,4 Long and extensive experience and the substantial data assembled from Ͼ25 centers worldwide have made septal myectomy an established and reliable strategy for patients of any age with HCM.…”
Section: Surgical Experiencementioning
confidence: 99%
“…Furthermore, only the surgical approach affords the flexibility under direct anatomic visualization that is often necessary to achieve complete repair and relief of subaortic obstruction, given the complex LV outflow tract morphology frequently encountered in HCM. 14 In contrast, alternative catheter-based techniques such as alcohol septal ablation are anatomically restricted to the size and distribution of the septal perforator coronary artery. 16 -19 Furthermore, accumulating evidence from nonrandomized studies indicates that myectomy also provides a long-term survival benefit that is indistinguishable from that of the general population and superior to nonoperated patients with obstruction and therefore may alter the natural history of HCM.…”
Section: Surgical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…4 However, excellent results were reported by others, using extended septal myectomy. 5 Alternatively, limited septal myectomy and patch reconstruction show good late results with a low operative risk. 3 …”
Section: Responsementioning
confidence: 99%